Implementasi Convolutional Neural Network Dengan MobileNetV2 Untuk Deteksi Tokoh Wayang Golek Berdasarkan Citra Digital - Siti Nurazizah; Asriyanik Asriyanik; Fathia Frazna Az-Zahra (STMIK Banjarbaru, 2025)
Wayang golek is a traditional Pasundan regional performing art played using wooden puppets by a puppeteer, which was recognized by UNESCO on November 7, 2003 as an intangible cultural heritage. However, many people find it difficult to distinguish the characters of wayang golek because of the diversity of the characters. This research aims to implement CNN in developing an image-based golek puppet character identification system, so that the recognition process is carried out quickly and accurately. This research uses 15 golek puppet characters with MobileNetV2 architecture as a feature extractor. The model produces train accuracy of 95% and validation accuracy of 91%. Evaluation results using confusion matrix showed accuracy of 90%, precision 90.47%, recall 90%, and f1-score 89.93%. The results show that the CNN model with MobileNetV2 architecture is effective and optimal in detecting and classifying puppets, so that it can support the preservation of puppet culture through technology.Keyword: Wayang Golek; Convolutional Neural Network; Computer Vision; Image Processing; Website AbstrakWayang golek adalah seni pertunjukan tradisional daerah Pasundan yang dimainkan menggunakan boneka kayu oleh seorang dalang, yang telah diakui UNESCO pada 7 November 2003 sebagai warisan budaya tak benda. Meskipun demikian, tidak sedikit orang kesulitan dalam membedakan tokoh-tokoh wayang golek karena keberagaman tokohnya. Penelitian ini bertujuan untuk mengimplementasikan CNN dalam mengembangkan sistem identifikasi tokoh wayang golek berdasarkan citra, sehingga proses pengenalan dilakukan secara cepat dan akurat. Penelitian ini menggunakan 15 tokoh wayang golek dengan arsitektur MobileNetV2 sebagai feature extractor. Model menghasilkan train accuracy sebesar 95% dan validation accuracy sebesar 91%. Hasil evaluasi menggunakan confusion matrix menunjukkan akurasi sebesar 90%, precision 90,47%, recall 90%, dan f1-score 89,93%. Hasil penelitian menunjukkan bahwa model CNN dengan arsitektur MobileNetV2 terbukti efektif dan optimal dalam mendeteksi serta mengklasifikasikan wayang golek, sehingga dapat mendukung pelestarian budaya wayang golek melalui teknologi.Kata kunci: Wayang golek; Convolutional neural network; Computer vision; Pengolahan citra; Website